KUALITAS LAYANAN DAN KEPUASAN PELANGGAN AKTIVITAS FREEHAND EXPORT PADA FREIGHT FORWARDER - Veronica Veronica; Alvin Senna; Devi Marlita (Institut Transportasi dan Logistik Trisakti, 2018)
The aim of this study is to analyze the correlation between freehand export service and customer satisfaction. Questionnaires were used to collect the data. The data was analysed using simple linear regression, coefficient correlation, coefficient determinant, and hypothesis test with T-test. The study was conducted in one of international freight forwarder companies. There were 76 participants as samples. The result of this study is that there is trig and positive relationship between freehand export service and customer service satisfaction which is shown on the coefficient relation of 0,785. Freehand export service has trig impact on customer satisfaction with coefficient value of 61.6%. T value is bigger than t-table. It is 10.9 > 1.66571. It means there is a significant correlation between freight forwarder and customer satisfaction.